2007
DOI: 10.1002/app.27120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of disinfection by microwave irradiation on the strength of intact and relined denture bases and the water sorption and solubility of denture base and reline materials

Abstract: This study evaluated the influence of microwave disinfection on the strength of intact and relined denture bases. Water sorption and solubility were also evaluated. A heat-polymerized acrylic resin (Lucitone 550) was used to construct 4-mm-thick (n 5 40) and 2-mm-thick (n 5 160) denture bases. Denture bases (2-mm) were relined with an autopolymerizing resin (Tokuso Rebase Fast, Ufi Gel Hard, Kooliner, or New Truliner). Specimens were divided into four groups (n 5 10): without treatment, one or seven cycles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…8,10,14,17 Despite the fact that the methods of disinfection through microwaves used in earlier studies 8,10,14,27 are considered to be effective for the sterilization of complete dentures and the treatment of denture stomatitis, it has been demonstrated that the heat generated during microwave irradiation can increase the contraction of the acrylic resins 28,29 and accelerate the water sorption and solubility processes of these materials. 30 There have also been reports of undesirable effects on mechanical properties in denture base resins after microwave disinfection for 6 minutes. [31][32][33][34] Therefore, in vitro and in vivo studies were conducted to evaluate both antimicrobial efficacy and effects on acrylic resins of microwave disinfection with the use of reduced irradiation times.…”
mentioning
confidence: 99%
“…8,10,14,17 Despite the fact that the methods of disinfection through microwaves used in earlier studies 8,10,14,27 are considered to be effective for the sterilization of complete dentures and the treatment of denture stomatitis, it has been demonstrated that the heat generated during microwave irradiation can increase the contraction of the acrylic resins 28,29 and accelerate the water sorption and solubility processes of these materials. 30 There have also been reports of undesirable effects on mechanical properties in denture base resins after microwave disinfection for 6 minutes. [31][32][33][34] Therefore, in vitro and in vivo studies were conducted to evaluate both antimicrobial efficacy and effects on acrylic resins of microwave disinfection with the use of reduced irradiation times.…”
mentioning
confidence: 99%
“…With a protocol of 720 W/5 minutes, another study showed a decrease in the flexural modulus [20] . The water sorption and solubility of complete denture bases in a previous study (650 W/6 minutes) showed no significant changes [13] . In the present study, both properties significantly decreased after microwave disinfection.…”
Section: Discussionmentioning
confidence: 64%
“…During microwave irradiation, the amount of unreacted monomer reduces due to further polymerization [10,18] , and the residual monomer released into water increases [21,22] . The heating generated could increase the water sorption, inducing a plasticizing effect that may affect the material [13] , besides the plasticizing effect of residual monomers [14] . All of these mechanisms must be considered as factors that can change the physical-mechanical properties of the acrylic resins [21] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a more clinically relevant approach, the effect of denture microwave disinfection on the maximum fracture load, deflection at fracture, and fracture energy of intact and relined denture bases was evaluated. After exposed to microwave irradiation for 7 days (6 minutes/650W), the strength of the denture bases was similar to the strength of those immersed in water for 7 days (Seó et al, 2008). An aspect that has also been investigated is the influence of microwave disinfection on bond strength between resilient liners and denture base acrylic resin.…”
Section: Effects On Physical and Mechanical Properties Of Dental Matementioning
confidence: 67%